Man Makes Himself - Childe, V. Gordon (Brill | Manohar Publishers & Distributors, 2024)
This seminal volume by V. Gordon Childe covers the prehistory period of the ancient world. Man Makes Himself covers the history of humanity and natural sciences. This title primarily covers the Neolithic period, when man gradually shifted from hunting to agriculture and cultivation practices. This book also covers the emergence and development of urbanization in major civilizations of the world, such as Mesopotamia, Egypt, and China etc. The author also discusses the rudimentary things that happened in the prehistoric age such as food-gathering methods, development of knowledge systems, growth and decline of urban centres, discovery of fire, tool technology that was used for hunting-gathering, and so forth. This book is of worth to scholars and students interested in the prehistory.